Effect of Substrate Preheating, Roughness and Particles Size on Splat Morphology of Thermal Sprayed Coatings - MOHAMED, Djeghdjough; EDDINE, Bacha; NACER, Dilmi (International Journal of Computational and Experimental Science and Engineering, 2015)
In thermal spraying process, a commercial powder is heated and accelerated simultaneously using a heat source and deposited in a molten or semi-molten condition on a prepared substrate. Coating quality highly depends on some important surface parameters such as the thermo-chemical and physical properties of both powder and substrate, the surface state, the preheated temperature, and the existence of oxidation. In pratice, it is commonly accepted that pre-heating the substrate, prior a thermal spray operation, have a great benefits to increase adhesion. However, this method is not routinely used. In this work, the preheating effect of XC18 steel substrates on the flattening behavior of two commercially available flame-sprayed powders was investigated in a temperature range from ambiant to 500 °C. The conventional flame spray gun was used to accelerate molten particles and Infra-red pyrometer was used to monitor the substrate temperature during a preheating process. Tthe coatings cross section microstructure and elements distribution was performed using SEM with EDS and optical microscope.